O conceito de lei revisitado. Reflexoes a proposito del Tratado constitucional europeu - Maria Lúcia Amaral (Araucaria)
According to article I-33 of the Treaty establishing a Constitution for Europe the legal acts of the Union will be the European laws, the European framework laws, the European regulations, the European decisions, recommendations and opinions. By using here the term law, the Convention that drafted the Treaty has chosen to appropriate a concept that until now has been exclusively a state-centered concept. Since there is not, however, a European state, the understanding of the language used by the Treaty asks for the revisitation of the concept of legal act, a central category of the European legal culture. This article focuses on the meaning that this concept has acquired in the Portuguese constitutional culture, as a part of the European legal culture.